Theranostic Pretargeting Drug Delivery and Imaging Platforms in Cancer Precision Medicine - Hapuarachchige, Sudath; Artemov, Dmitri (Frontiers in Oncology, 2020)
Theranostics are nano-size or molecular-level agents serving for both diagnosis and therapy. Structurally, they are drug delivery systems integrated with molecular or targeted imaging agents. Theranostics are becoming popular because they are targeted therapeutics and can be used with no or minimal changes for diagnostic imaging to aid in precision medicine. Thus, there is a close relation between theranostics and image-guided therapy (IGT), and theranostics are actually a subclass of IGT in which both therapeutic and imaging functionalities are attributed to a single platform. An important theranostics strategy is biological pretargeting. In pretargeted IGT, first, the target is identified by a target-specific natural or synthetic bioligand followed by a nano-scale or molecular drug delivery component, which form therapeutic clusters by in situ conjugation reactions. If pretargeted drug delivery platforms are labeled with multimodal imaging probes, they can be used as theranostics for both diagnostic imaging and therapy. Optical and nuclear imaging techniques have mostly been used in proof-of-concept studies with pretargeted theranostics. The concept of pretargeting in theranostics is comparatively novel and generally requires a confirmed overexpression of surface receptors on targeted cells/tissue. In addition, the receptors should have natural or synthetic bioligands to be used as pretargeting components. Therefore, applications of pretargeting theranostics are still limited to several cancer types, which overexpress cell-surface markers on the target cancer cells. In this review, recent discoveries of pretargeting theranostics in breast, ovarian, prostate, and colorectal cancers are discussed to highlight main strengths and potential limitations the strategy.